2007
DOI: 10.1002/jcb.21247
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and mitochondrial function: Molecular replacement and antioxidant supplements to prevent membrane peroxidation and restore mitochondrial function

Abstract: Metabolic syndrome consists of a cluster of metabolic conditions, such as hypertriglyceridemia, hyper-low-density lipoproteins, hypo-high-density lipoproteins, insulin resistance, abnormal glucose tolerance and hypertension, that-in combination with genetic susceptibility and abdominal obesity-are risk factors for type 2 diabetes, vascular inflammation, atherosclerosis, and renal, liver and heart disease. One of the defects in metabolic syndrome and its associated diseases is excess cellular oxidative stress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 162 publications
(213 reference statements)
1
84
0
11
Order By: Relevance
“…Accumulating evidence suggests that this indeed may be the case in diseases of the nervous system such as Parkinson's, Alzheimer's and Huntington's, and amyotrophic lateral sclerosis (for reviews, see Lin and Beal, 2006;Schapira, 2006;Whitton, 2007). Although it is likely that such a defect may occur in other conditions associated with inflammation, such as metabolic syndrome or diabetes mellitus, the evidence is at present contradictory (Mogensen et al, 2007;Boushel et al, 2007;Nicolson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that this indeed may be the case in diseases of the nervous system such as Parkinson's, Alzheimer's and Huntington's, and amyotrophic lateral sclerosis (for reviews, see Lin and Beal, 2006;Schapira, 2006;Whitton, 2007). Although it is likely that such a defect may occur in other conditions associated with inflammation, such as metabolic syndrome or diabetes mellitus, the evidence is at present contradictory (Mogensen et al, 2007;Boushel et al, 2007;Nicolson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We, as well as others, have previously suggested that elevated glucose levels can cause altered gene expression in vascular and islets cells (14)(15)(16)(17) (18). He also reported that these genes were differentially regulated by high (22 mM) compared to low glucose (5.5 mM) concentrations.…”
Section: Introductionmentioning
confidence: 62%
“…In 2005, Brownlee put forward a hypothesis linking these pathogenic mechanisms, explaining the overproduction of superoxide by the mitochondrial electron transport chain (23). For example, hyperglycemiainduced oxidative stress promotes the formation of advanced glycation end products, PKC activation, hexosamine and polyol pathway activity (18,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Since reactive oxygen species (ROS) produced by mitochondria are implicated in development of metabolic diseases (9,33), Prx3 may play a protective role in regulating adipocytes. The body weights of wild-type (WT) and Prx3 KO mice were indistinguishable at the 4-month period.…”
Section: Prx3 Ko Mice Display Larger Fat Pads With Hypertrophied Adipmentioning
confidence: 99%
“…However, histology showed that adipocytes were significantly larger in Prx3 KO mice. Hypertrophied adipocytes due to enlarged lipid droplets are frequently observed in mice models of obesity (17) and these cells exhibit impaired mitochondrial function and insulin signaling along with higher ROS levels (10,18,33).…”
Section: Fig 4 Protein Expression Profiles Of Adipocytes Obtained Fmentioning
confidence: 99%